Improving Reading Comprehension of Narrative text by Using L-B-A (Literature-based Approach) at the Ninth-grade students of SMP Negeri 1 Nunukan - Nindya Yunisah; Arifin Arifin; Ridwan Ridwan (Naifaderu Cipta Sejahtera, 2023)
Purpose This research aimed to find out whether teaching ninth-grade students at SMP Negeri 1 Nunukan using a literature-based Approach can significantly improve their reading comprehension of narrative texts. Methodology Classroom Action Research (CAR) will be used for the study. The process of this action research is based on the Kemmis and Taggert paradigm. The concept of classroom action research-based instruction emphasizes that the research process has two connected components: the research process and the research output. This stage is completed with the intention of improving numerous flaws before re-implementing it in the subsequent cycle. It is divided into two cycles, each of which comprises four stages: preparation, execution, observation, and reflection. Results/Findings In this study, the pupils' reading comprehension skills in English improved and advanced. From the first cycle to the second cycle, it is discernible. Each cycle sees an improvement in the students and teacher activity. The teacher and students’ observation sheet in each meeting reach the criteria of success. The score from the observation sheet must reach a score of 80 or above to achieve the criteria of success. The minimum score has been determined and agreed by researcher and teacher collaborator. For the first cycle I to cycle II, the score for teacher teaching activities has increased. The observation sheet from the teachers and pupils was used by the researcher as backup information. Each meeting's observation form both the teacher and students meet the standards for success. Implication The study indicates significant enhancement in students' English reading comprehension skills across cycles, evident in discernible progress from the initial to subsequent phases. Consistent improvements in both student engagement and teaching activities are notable, meeting success criteria set in the observation sheets with a threshold of 80 points, a benchmark agreed upon by researchers and teacher collaborators.